Nature of the metal-insulator transition in few-unit-cell-thick LaNiO3 films - M. Golalikhani (Nature Portfolio, 2018)
The electronic behaviour of complex oxides such as LaNiO3 depends on many intrinsic and extrinsic factors, making it challenging to identify microscopic mechanisms. Here the authors demonstrate the influence of oxygen vacancies on the thickness-dependent metal-insulator transition of LaNiO3 films.